PENGARUH STRUKTUR MODAL, STRUKTUR ASET DAN PERTUMBUHAN PENJUALAN TERHADAP HARGA SAHAM DENGANRETURN ON ASSETS - Prasetyo, Dwi; Halim, Abdul; Sari, Ati Retna (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2017)
This study aims to examine and explain the effect of capital structure, asset structure and sales growth on share prices with return on assets (ROA) as a mediating variable in manufacturing companies listed on the Indonesia Stock Exchange in the period 2014-2015. The type of research used is explanatory research, by testing classic assumptions, and analyzed using path analysis, and using the t test. The number of samples is 36 companies, and the sample collection method used is the random method. This research variable consists of capital structure, asset structure and sales growth as an independent variable, stock price as the dependent variable, and ROA as a mediating variable. The analysis shows that partially capital structure, asset structure and sales growth affect ROA. Capital structure, asset structure and sales growth affect stock prices. Sales growth influences stock prices through ROAand the effect is greater. Capital structure influences stock prices through ROA but the effect is smaller. Asset structure influences stock prices through ROA but the effect is more small.